Valid but Invalid: Suboptimal ImPACT Baseline Performance in University Athletes. Issue 7 (July 2018) - WALTON, SAMUEL R.; BROSHEK, DONNA K.; FREEMAN, JASON R.; CULLUM, C. MUNRO; RESCH, JACOB E.
ABSTRACT: Purpose: This study aimed to investigate the frequency of valid yet suboptimal Immediate Postconcussion Assessment and Cognitive Test (ImPACT) performance in university athletes and to explore the benefit of subsequent ImPACT administrations. Methods: This descriptive laboratory study involved baseline administration of ImPACT to 769 university athletes per the institution's concussion management protocol. Testing was proctored in groups of ⩽2 participants. Participants who scored below the 16th percentile according to ImPACT normative data were readministered the ImPACT test up to two additional times because these scores were thought to be potentially indicative of suboptimal effort or poor understanding of instructions. Descriptive analyses were used to examine validity indicators and individual Verbal and Visual Memory, Visual Motor Speed, and Reaction Time ImPACT composite scores in initial and subsequent administrations. Results: On the basis of ImPACT's validity criteria, 1% (9/769) of administrations were invalid and 14.6% (112/769) had one or more composite score of <16th percentile but were considered valid. After one readministration, 71.4% (80/112) achieved scores of ≥16th percentile and an additional 18 of 32 scored ≥16th percentile after a third administration. Verbal Memory was most commonly <16th percentile on the first administration (43%), Verbal Memory and Visual Motor Speed on the second administration (44% each), and Visual Motor Speed alone on the third administration (50%). Conclusions: Approximately 16% of ImPACT records were flagged as invalid or had one or more composite scores of <16th percentile, potentially indicative of suboptimal performance. Upon readministration, 88% of those participants scored >16th percentile. Clinicians must be aware of suboptimal ImPACT performance as it limits the clinical utility of the baseline assessment. Further research is needed to address factors leading to "valid" but invalid baseline performance.